A educação crítica em Adorno e a vigilância sobre a educação no Brasil - Melo, Demétrio Alves de (2022)
This investigation goes through central themes related to the concepts of authoritarian personality, emancipatory education, mass propaganda and psychology. The aforementioned analysis axes intertwine and question the current brazilian scenario, looking to understand its sociopolitical circumstances. Working under general and particular approaches, it is possible to highlight some of the main influences coming from those narratives and bring up hypotheses on how deep authoritarian ideologies go into the educational environment. It was intended to discuss the hypothesis on the degree of influence the authoritarian character ideologies, so prominent today, have had in projects that seeked control over teaching institutions’ teaching process and methodologies. To reach such goal, a critical analysis of the inherent contradictions to the educational process is necessary, to understand the means and instruments the authoritarian discourse has gained ground with, even in the field where said educational process should be the leading force on fighting it. The dialectic historical method will be adopted, supported by a bibliographical and quality research, where there is a predominance of interpretations of the researched phenomena and their subsequent attribution of meanings. Having as guide the current clash dynamics in brazilian education’s core, the objective is to identify the authoritarian ideological essence that constitutes essentially the scope of the School Without Parties project and what are its strategies to influence the guidelines that conduct the current educational model in Brazil. Regarding the procedures, a deep reapproach was conducted on written material about the sensitive themes that will be compared to documents that demonstrate the authoritarian and wishful character for control, promoted by brazilian government’s current conservative educational system. Equipped mainly with the approach developed by Theodor Adorno about the danger of returning authoritarian movements, it was possible to elaborate an understanding of the psychoanalytic elements that feed the so called authoritarian personality adopted by a few groups who are predisposed to such ideologies. Once the authoritarian character present on those movements is identified, it is possible to investigate how these authoritarian ideologies materialize in conservative rooted projects by the current brazilian government. Thus, the research challenges itself to present the elements that provide basis to the current authoritarian ideal, how masses absorb those ideologies, their influence on the school core and the ways to fight them.